The Impact of Self-determination Motivation on Academic Achievement in the Context of Knowledge-Oriented Short-Video Learning - Du, Baiyan; Lai, Yuege (Education Insights, 2026)
In recent years, the ways individuals acquire knowledge and information have evolved significantly, with short video platforms increasingly incorporating educational content and becoming widely used tools for learning. Although prior studies have confirmed the effectiveness of short video–based learning, the role of self-determination motivation in this context remains insufficiently examined compared with traditional online learning environments. Grounded in knowledge-oriented short video learning, this study explores how college students’ self-determination motivation influences cognitive academic achievement, focusing on the mediating roles of goal orientation and self-regulated learning strategies. Survey data collected from 505 university students with short video learning experience indicate that self-determination motivation positively predicts goal orientation, self-regulated learning strategies, and cognitive academic achievement, and further enhances cognitive academic achievement through the mediating effects of goal orientation and self-regulated learning strategies. These findings provide theoretical support for improving learning effectiveness in short video learning contexts and offer empirical evidence for the appropriate and optimized use of this instructional approach.